'Adieu, adieu, remember me!': whatever happened to poetry memorisation in schools?. (3rd April 2022) - Jaques, Zoe; Whitley, David
ABSTRACT: The practice of memorising poems has commonly been perceived as outdated in recent years. By the 1980s, indeed, learning poems by heart frequently headed up a list of old-fashioned pedagogies deemed responsible for turning young people off poetry. Yet it would be hard to overestimate how enormous a gap this opened up with the core assumptions that had guided the teaching of literature for hundreds (perhaps even thousands) of years before. This article re-examines some of the assumptions that led to the wide-scale rejection of this ancient practice. This is not necessarily to urge a wholesale restitution of poetry memorisation and recitation in our secondary schools. Rather, in revisiting arguments for the value of the memorised poem, we hope to shed fresh light on the degree and form of its continued relevance for contemporary contexts and educational practices.